Molecular Imaging: a Novel Tool To Visualize Pathogenesis of Infections In Situ - Gordon, Oren; Ruiz-Bedoya, Camilo A.; Ordonez, Alvaro A.; Tucker, Elizabeth W.; Jain, Sanjay K. (mBio, 2019)
Molecular imaging is an emerging technology that enables the noninvasive visualization, characterization, and quantification of molecular events within living subjects. Positron emission tomography (PET) is a clinically available molecular imaging tool with significant potential to study pathogenesis of infections in humans. Molecular imaging is an emerging technology that enables the noninvasive visualization, characterization, and quantification of molecular events within living subjects. Positron emission tomography (PET) is a clinically available molecular imaging tool with significant potential to study pathogenesis of infections in humans. PET enables dynamic assessment of infectious processes within the same subject with high temporal and spatial resolution and obviates the need for invasive tissue sampling, which is difficult in patients and generally limited to a single time point, even in animal models. This review presents current state-of-the-art concepts on the application of molecular imaging for infectious diseases and details how PET imaging can facilitate novel insights into infectious processes, ongoing development of pathogen-specific imaging, and simultaneous in situ measurements of intralesional antimicrobial pharmacokinetics in multiple compartments, including privileged sites. Finally, the potential clinical applications of this promising technology are also discussed.